The Holy Spirit and the eagle feather : the struggle for Indigenous Pentecostalism in Canada - Ross, Aaron A. M. (Montreal ; Kingston ; London ; Chicago : McGill-Queen's University Press, 2023)
"Pentecostalism is one of the fastest-growing religious movements in the world. In Canada, it is the most rapidly growing Christian group among Indigenous people, with approximately one in ten Pentecostals in the country being Indigenous. Pentecostalism has become a religious force in many Indigenous communities, where congregations are most often led by Indigenous ministers - an achievement that took many decades. The Holy Spirit and the Eagle Feather traces the development of Indigenous Pentecostalism in Canada. Exploring the history of twentieth-century missionization, with particular attention to the Pentecostal Assemblies of Canada's Northland Mission, founded in 1943, Aaron Ross shows how the denomination's Euro-Canadian leaders, who believed themselves to be supporters of Indigenous-led churches, struggled to relinquish control of mission management and finances. Drawing on interviews with contemporary figures in the movement, he describes how Indigenous Pentecostals would come to challenge the mission's eurocentrism over decades, eventually entering positions of leadership in the church. This process required them to confront the painful vestiges of colonialism and to grapple with the different philosophies and theologies of Pentecostalism and Indigenous traditional spiritualities. In doing so they indigenized the movement and forged a new identity, as Indigenous and Pentecostal. Indigenous Pentecostals now occupy key roles in the church and serve as political, cultural, and economic leaders in their communities. The Holy Spirit and the Eagle Feather tells the story of how they overcame the church's colonial impulses to become religious leaders, as well as agents for decolonization and reconciliation."--
Introduction -- The Indigenous principle : the Pentecostal assemblies of Canada and its missiology -- Pentecostalism's place : positioning the Pentecostal assemblies of Canada within the encounter between Euro-Canadian missionaries and Indigenous people -- The heavens have become a highway : how aviation indirectly enabled a PAOC mission to Indigenous people -- Leadership qualities and the call of God for the ministry : the Northland Mission Bible College and PAOC ministerial credentials -- Contention and contextualization : tensions between Euro-Canadian missionaries and Indigenous ministers -- Standing at the shoreline : the dissolution of the Northland Mission and the birth of Aboriginal Pentecostal ministries -- Past, present, and future : the fruition of the Indigenous principle in the age of apology, truth, and reconciliation -- Conclusion-- Breaking new ground : Indigenous Pentecostalism in the twenty-first century and its significance for the majority world.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on September 06, 2023).
eBooks on EBSCOhost
Keywords: Indigenous peoples -- Canada -- Religion; Pentecostalism -- Canada; Pentecostals -- Canada; First Nations Pentecostals; Peuples autochtones -- Canada -- Religion; Mouvement charismatique -- Canada; Pentecôtistes -- Canada; RELIGION / Christianity / Pentecostal & Charismatic; Indigenous peoples -- Religion; Pentecostalism; Pentecostals; Canada; Aboriginal; Assemblies; Christianity; Indian Residential Schools; Inuit; Metis; Native; North America; Pentecostal; Studies; acquisition; anthropology; apology; colonialism; cosmology; decolonization; ethnography; history; indigenization; language; majority; migration; postcolonialism; reconciliation; religion; spiritualities; theology; traditional; transnationalism; truth; world